Early attenuation of autonomic nervous function in senescence accelerated mouse-prone 8 (SAMP8) - Chikamoto, Akitoshi (Exp Anim, 2019)
The senescence-accelerated mouse (SAM) strain has been established as an inbred strain with an accelerated aging phenotype. SAM prone-8 (SAMP8), one of the SAM strain, exhibits learning disability, immune deficiency, and circadian rhythm loss at a relatively young age. However, it has not been clarified whether aging affects the autonomic nervous activity in SAMP8. The aim of this study was to clarify the utility of SAMP8 in age-related studies of autonomic nervous function. Electrocardiogram (ECG), body temperature, and locomotor activity were recorded to evaluate bio-behavioral activities. Autonomic nervous activity was evaluated via power spectral analysis of heart rate variability from ECG recordings. SAMP8 significantly decreased both biological and autonomic nervous functions, and the animals exhibited circadian rhythm loss of locomotive activity at as early as 40 weeks of age compared with a control strain at the same age. We concluded that the SAMP8 strain can be used as an animal model for age-related studies of autonomic nervous function.